Multi-omics of a model bacterial consortium deciphers details of chitin decomposition in soil - Ryan McClure; Albert Rivas-Ubach; Kim K. Hixson; Yuliya Farris; Marci Garcia; Robert Danczak; Michelle Davison; Vanessa L. Paurus; Janet K. Jansson (mBio, 2025)
ABSTRACT Soil microorganisms interact to carry out decomposition of complex organic carbon and nitrogen compounds, such as chitin, but the high diversity and complexity of the soil microbiome and habitat have posed a challenge to elucidating such interactions. Here, we sought to address this challenge by analysis of a model soil consortium (MSC-2) consisting of eight soil bacterial species. Our aim was to elucidate the specific roles of the member species during chitin metabolism. Samples were collected from MSC-2 incubated in chitin-enriched soil over 3 months. Multi-omics was used to understand how the community composition, transcripts, proteins, and chitin decomposition shifted over time. The data clearly and consistently revealed a temporal shift during chitin decomposition with defined contributions by individual species. A Streptomyces genus member (sp001905665) was a key player in early steps of chitin decomposition, with other MSC-2 members being central in carrying out later steps. These results illustrate how multi-omics applied to a defined consortium untangles the interactions between soil microorganisms.IMPORTANCEAlthough soil microorganisms carry out decomposition of organic matter in soil, the details are unclear due to the complexity of the soil microbiome and the heterogeneity of the soil habitat. Understanding carbon decomposition is of vital importance to determine how the soil carbon cycle functions. This is especially important with regard to understanding the fertility of soils and their ability to support plant growth. To overcome these challenges, we investigated in considerable detail a model soil community during its decomposition of a typical soil organic molecule—chitin. By using a multi-omics approach, we were able to decipher community interactions during chitin breakdown. This information provides a basis for understanding how more complex soil microbial communities interact in nature.